Mosque and Environmental Issues: A Research Path Analysis - As-Salafiyah, Aisyah; Uula, Mimma Maripatul; Taufiq, Muhammad (Journal of Islamic Economics Literatures, 2024)
Mosques play an important role in the social structure of Muslim communities. Mosque functions are not only limited to religious functions, but also play an important role in addressing various social problems faced by the community as well as environmental issues, such as raising awareness and knowledge related to environmental cleanliness, energy resources, and waste management, where these roles are integrated with Islamic principles. The purpose of this study is to see the development of research on the topic of "Mosque and Environment" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data derived from the Scopus database with a total of 539 journal articles and the keywords used in data retrieval are "Mosque and Environment". Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of research development "Mosque and Environment". The results of the study found that in bibliometric author mapping, the authors who published the most research on the theme "Mosque and Environment" were Yüksel A.; Arici M.; Krajčík M.; Mortada H.A.; Baleha M.; Kuppinger P.; Oparin, D.; Sert F.Y.; Karaman Ö. Y.; and Barik R.K.Furthermore, based on bibliometric keyword mapping, there are 4 clusters with dominating words, namely building, system, strategy, use, mosque, person, culture, and element. Furthermore, the topics of research lines related to Mosque and Environment are Energy consumption strategies in mosque buildings, Effects of mosque-based environmental knowledge programs, Societal relations and mosque environmental impact, and Muslim community responses to mosque environmental issues.